L'image du corps : étude des forces constructives de la psyché - Schilder, Paul, 1886-1940; Gantheret, François, 1934-2018; Truffert, Paule; Gantheret, François, 1934-2018 (Paris : Gallimard, 1977)
Hoe komen we tot het beeld dat we van onszelf hebben?